2007
DOI: 10.1164/rccm.200610-1441oc
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms in the First 7 Years of Life and Birth Weight at Term

Abstract: A lower birth weight in children born at term is associated with a transiently increased risk of respiratory symptoms. This effect is enhanced by environmental tobacco smoke exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 31 publications
5
70
0
1
Order By: Relevance
“…We measured the main respiratory symptom outcome in our study using International Study on Asthma and Allergy in Childhood questionnaires. Although this method is validated from the age of 7 years, it is widely accepted in epidemiological studies among younger children [32][33][34] , and reliably reflects the incidence of asthma symptoms in young children. 35 An earlier Dutch birth cohort study used identical International Study on Asthma and Allergy in Childhood questions, and observed similar prevalences of wheezing based on the International Study on Asthma and Allergy in Childhood questionnaires as in our study.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the main respiratory symptom outcome in our study using International Study on Asthma and Allergy in Childhood questionnaires. Although this method is validated from the age of 7 years, it is widely accepted in epidemiological studies among younger children [32][33][34] , and reliably reflects the incidence of asthma symptoms in young children. 35 An earlier Dutch birth cohort study used identical International Study on Asthma and Allergy in Childhood questions, and observed similar prevalences of wheezing based on the International Study on Asthma and Allergy in Childhood questionnaires as in our study.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
“…35 An earlier Dutch birth cohort study used identical International Study on Asthma and Allergy in Childhood questions, and observed similar prevalences of wheezing based on the International Study on Asthma and Allergy in Childhood questionnaires as in our study. 32 In preschool children, a diagnosis of asthma is based on symptoms. Objective tests, including spirometry or bronchial hyper responsiveness, are difficult to perform in young children and have limited applicability.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
“…Preterm birth has been consistently associated with a higher prevalence of wheezing illness and deficits in lung function measures in childhood (14,15) . Early life diet could modulate the likelihood of childhood asthma by affecting fetal airway development and/or influencing the initial early life interactions between allergens and the immune system by promoting Th-cell differentiation towards the Th2 cell type (16) .…”
Section: Maternal Diet During Pregnancymentioning
confidence: 99%
“…[3][4][5][6][7][8] The risks of these infectious diseases are affected by several factors including birth weight, gestational age, socioeconomic status, ethnicity, number of siblings, day care attendance, and parental smoking. 3,5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20] Breastfeeding has been suggested as a modifiable influencing factor. When given exclusively, breastfeeding reduces the risk of infectious diseases in infants in developing countries.…”
mentioning
confidence: 99%